2021
DOI: 10.3390/app11167726
|View full text |Cite
|
Sign up to set email alerts
|

The Experimental Study of Innovative Methods Regarding the Removal of Sm(III)

Abstract: The modern development of the construction materials sector determines the use of rare earth metals (REM) for various purposes. In particular, REM are added as basic alloying elements into magnesium alloys to increase alloy durability and strength. The complex systematic study of structural components and REM interaction are the basis for the phase state monitoring of multicomponent oxide polyfunctional materials. In addition, on the preparatory stage, layers with specified construction material coatings are f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 30 publications
(43 reference statements)
0
5
0
Order By: Relevance
“…The experimental study was carried out using a laboratory flotation machine FMP-L1 manufactured by Vektis Minerals (Russia) under following conditions: a volume of flotation capacity of 0.5 L, a mass of the suspension of ore of 50 ± 0.01 g, 90% grain size less than 183 μm, the speed of the impeller of 1000 rpm with an air flow of 3.8 m 3 /min, and stirring the suspension for 1 min. Flotation was carried out for 6 min. The float and sink products were filtered, washed, dried, and weighed. Equation was used to calculate the extraction degree where m 0 is the mass of the initial sample of ore and m 1 is the mass of the washed and dried foam product.…”
Section: Methodsmentioning
confidence: 99%
“…The experimental study was carried out using a laboratory flotation machine FMP-L1 manufactured by Vektis Minerals (Russia) under following conditions: a volume of flotation capacity of 0.5 L, a mass of the suspension of ore of 50 ± 0.01 g, 90% grain size less than 183 μm, the speed of the impeller of 1000 rpm with an air flow of 3.8 m 3 /min, and stirring the suspension for 1 min. Flotation was carried out for 6 min. The float and sink products were filtered, washed, dried, and weighed. Equation was used to calculate the extraction degree where m 0 is the mass of the initial sample of ore and m 1 is the mass of the washed and dried foam product.…”
Section: Methodsmentioning
confidence: 99%
“…Similar to ion flotation, NaDDS is frequently used as the surfactant in solvent sublation. Several authors have obtained 99% separation efficiency using this technique at pH 7-8 [138,139,144,145].…”
Section: Solvent Sublationmentioning
confidence: 98%
“…However, the majority of ion flotation studies used sodium dodecyl sulfate (NaDDS) as the surfactant (Table 4). Previous studies have shown that this technique could recover low-concentration REEs (10 -6 to 10 -3 M) with efficiencies of 57-98% [133][134][135][136][137][138][139][140]. Aside from NaDDS, other surfactants like monorhamnolipid [131,140], AKYPO RO 90 VG [141], and cetylpyridinium chloride (CPC) [142] have also been used.…”
Section: Ion Flotationmentioning
confidence: 99%
See 1 more Smart Citation
“…The need to increase the content of useful components in rougher flotation is determined by a relationship between the content of the recovered component in the feedstock, its extraction and quality of the concentrate. In practice, this is resolved by the structure of the separation cascade [11][12][13] which is commonly arranged in such a way [14][15][16], that the necessary pulp beneficiation is achieved by rerecycling the middlings. In the canonical circuit [17][18][19], tailings of primary cleaning and recleaner flotation concentrate [20][21][22] are recycled to rougher flotation, which leads to an increasing content of recoverable mineral [23,24] at the expense of its difficult-to-float (persistent) forms.…”
Section: Ui K T T Ui Kt Ktmentioning
confidence: 99%